FORMULASI CAMPURAN TEPUNG SAGU BARUK (Arenga microcarpa) DAN UBI JALAR KUNING (Ipomoea batatas) DALAM PEMBUATAN BOLU GULUNG - Angel Basare; Erny Nurali; Tineke Langi (COCOS, 2015)
ABSTRACT Sago baruk flour and yellow sweet potato are commodities of highly potential to be developed for the making of food product find rolled spongecake. This research is aimed to define the proper formula, to implement the proximate analysis and to calculate the calorie value of the rolled spongecake from the mixture of sago flour and yellow sweet potato that impressed the panelists. This research uses the Complete Randomized Design method by treating the sago flour and yellow sweet potato. The result organoleptic test: the chosen treatment is followed by chemical quality analysis. The chosen treatment is E = (30% of sago flour :Â  70% yellow sweet potato). The result of chemical analysis of the chosen rolled spongecake: chemical composition are 10,75% water, 1,70% ash, 20,84% protein, 7,33% protein, and 59,40% total carbohydrate. The total energy is 454,42 Kkal. Â Keywords : Sago baruk flour, Yellow sweet potato, Rolled spongecake